Estudo da incorporação de nanocelulose no cimento odontológico ionômero de vidro - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Conventional glass ionomer cement is a versatile restorative material in dentistry. It has excellent properties such as fluoride release and adhesion to tooth structure, however it does not have good mechanical resistance. This limitation does not allow its use in areas of great masticatory effort. A nanocellulose has been used as a reinforcing agent in different types of materials. Its use in the biomedical and dental field is due to its ability to reinforce the composite matrix. A nanocellulose can be extracted in the form of nanocrystals (CNC). Thus, the aim of this work was to evaluate whether the addition of CNC improves the mechanical properties of the material. The specimens were made, divided into groups containing the percentage by weight of CNC (0.2%, 0.4% and 0.6%) and a control group (without modifications). The characterization techniques were FTIR and DRX. The active FTIR that there is no difference in bindings between the GC and the groups with addition. They were evaluated as mechanical properties of the cement after 24 hours by compressive strength and tensile strength by diametrical compression tests. The results were treated and plotted, obtaining the stress X strain graphs, the mean of each group of points of maximum strain, where the CG presented mean and standard deviation of 91.52 (3.36) MPa; 0.2% of 109.11 (10.51) MPa; 0.4% of 93.19 (1.97) MPa and 0.6% 76.63 (8.49) MPa. Data were dissipated through analysis of variance (ANOVA) and significant differences between groups. The group with the addition of 0.2% mean presentation of 109.11 (± 10.51) MPa, being the best group, an increase of 19% when compared to the control group. The group with the addition of 0.4% an increase of 1.8% and the 0.6% group a decrease of 16%.
Keywords: Cimentos dentários de ionômero de vidro; Materiais dentários; ENGENHARIAS: ENGENHARIA DE MATERIAIS E METALURGICA: MATERIAIS NAO METALICOS; Ionômero de Vidro; Nanocristais de Celulose; Resistência à Compressão; Drx; Ftir